2017
DOI: 10.1002/jcp.25891
|View full text |Cite
|
Sign up to set email alerts
|

Swelling‐induced chloride current in glioblastoma proliferation, migration, and invasion

Abstract: Glioblastoma (GBM) remains as the most common and aggressive brain tumor. The survival of GBM has been linked to the aberrant activation of swelling-induced chloride current I Cl,swell . In this study, we investigated the effects of I Cl,swell on cell viability, proliferation, and migration in the human GBM cell lines, U251 and U87, using a combination of patch clamp electrophysiology, MTT, colony formation, wound healing assays and Western immunoblotting. First, we showed that the specific inhibitor of I Cl,s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 28 publications
2
36
2
Order By: Relevance
“…Since the molecular identities of the swelling-induced Clchannels remain elusive, we first measured the electrophysiological properties of the swelling-induced Clcurrent I Cl,swell in primary neurons and pharmacologically verified with DCPIB ( Figure 1). When exposed to 30% hypotonic solution, there was activation of swelling-induced Clcurrent I Cl,swell , with a reversal potential that is consistent with what we previously reported [18] . In the continued presence of the hypotonic solution, application of DCPIB (10 μmol/L) inhibited the activated current ( Figure 1A and 1B).…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…Since the molecular identities of the swelling-induced Clchannels remain elusive, we first measured the electrophysiological properties of the swelling-induced Clcurrent I Cl,swell in primary neurons and pharmacologically verified with DCPIB ( Figure 1). When exposed to 30% hypotonic solution, there was activation of swelling-induced Clcurrent I Cl,swell , with a reversal potential that is consistent with what we previously reported [18] . In the continued presence of the hypotonic solution, application of DCPIB (10 μmol/L) inhibited the activated current ( Figure 1A and 1B).…”
Section: Resultssupporting
confidence: 90%
“…Recordings were carried out in the whole-cell configuration using the Axopatch 700B (Axon Instruments, Inc), similar to our previous studies [18,[29][30][31] . The ramp protocol was from -100 to +100 mV (400 ms; -70 mV holding; 5 s interval at 2 kHz; digitized at 5 kHz).…”
Section: Patch Clamp Electrophysiologymentioning
confidence: 99%
See 1 more Smart Citation
“…Uncover the underlying molecular mechanisms of gliomas is an important way to control tumor progress. Previous studies have demonstrated signal pathways such as lipid metabolism disorder, stress-induced cell death, and ion channel in gliomas (Leaver, Rizzo, & Whittle, 2010;Wong et al, 2018;Wong, Turlova, Feng, Rutka, & Sun, 2017). In recent years, the roles of lncRNAs in the pathophysiological process of gliomas have been F I G U R E 4 The overlapped differentially expressed genes in datasets GSE40687 and GSE4290.…”
Section: Discussionmentioning
confidence: 99%
“…20 Liu et al 22 showed that ClC-3 activators with potent antitumor activities inhibited the PI3K/AKT/mTOR signaling pathway. In contrast, Wong et al 23 showed that the Cl − channel inhibitor exerted suppressive effects on the PI3K/AKT and JAK/STAT3 signaling pathways. HER2 is an attractive therapeutic target for gastric, colorectal, and ovarian cancers, and the STAT3 signaling pathway is associated with the high expression of HER2 in ovarian cancer.…”
mentioning
confidence: 91%